2010
DOI: 10.1093/pubmed/fdq048
|View full text |Cite
|
Sign up to set email alerts
|

Changes in travel-related carbon emissions associated with modernization of services for patients with acute myocardial infarction: a case study

Abstract: Introducing pPCI to manage STEMI patients results in substantial carbon emissions increase. Environmental profiling of service modernization projects could motivate carbon control strategies, and care pathways design that will reduce patient transport need. Healthcare planners should consider the environmental legacy of quality improvement initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…29 Other clinical innovations, however, may increase patient travel. Replacing thrombolysis in local hospitals with interventional cardiological procedures in more distant, larger hospitals will increase ambulance CO 2 emissions, 30 highlighting conflicts that can arise between protecting the patient and the environment. 23…”
Section: Resultsmentioning
confidence: 99%
“…29 Other clinical innovations, however, may increase patient travel. Replacing thrombolysis in local hospitals with interventional cardiological procedures in more distant, larger hospitals will increase ambulance CO 2 emissions, 30 highlighting conflicts that can arise between protecting the patient and the environment. 23…”
Section: Resultsmentioning
confidence: 99%
“…This study illustrates how methods developed for use in other sectors can be implemented in the healthcare setting. While previous studies have considered emissions arising from particular components of a healthcare pathway, 23–26 this study is, we believe, the first carbon footprint of a pathway to also include both the direct and indirect emissions attributable to the treatment itself. This study, therefore, provides a methodological template for future evaluation of the emissions of other treatments and care pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The emissions attributable to the travel of staff and patients have been included to maintain consistency with previous studies undertaken within the health care setting, [6][7][8] including the NHS England Carbon Footprinting Study, 5 although PAS2050 would suggest the exclusion of those emissions associated with the travel of employees and consumers. 19 Exclusions To maintain consistency with PAS2050, 19 the following sources of GHG emissions were excluded from the analysis: buildings and construction; sterilisation procedures; human inputs into processes; the capital cost of machinery used repeatedly; food and beverages for staff; scientific research; staff training; business services; and immaterial emissions sources (those anticipated to be o1% of the total emissions).…”
Section: Boundary Settingmentioning
confidence: 99%
“…Carbon footprinting studies with varying methodological approaches and complexity are now being reported within the medical literature. [6][7][8][9][10][11][12][13] The importance of sustainability within the delivery of ophthalmic care has been considered previously, 14,15 and the emissions attributable to small incision cataract surgery have been argued to be smaller than those arising from phacoemulsification. 16 Cataract surgery is a commonly performed surgical procedure within the NHS in England with over 300 000 operations undertaken annually making it an ideal target for reducing emissions.…”
Section: Introductionmentioning
confidence: 99%